Structured Oral Examinations in Internal Medicine - Case G - Hani Almoallim; Ali Alkatheeri; Alaa Monjed; Fozya Basheer; Abdullah Tawakol; Ahmad Imam; Abdulalsalam Noorwali; Kamran Hameed (Association of American Medical Colleges, 2009)
Abstract This resource is one component of the nine-part Structured Oral Examinations in Internal Medicine series. In this case (Case G: Asthma), a 45-year-old Saudi female teacher complains of recurrent breathlessness for the past 2 years, increasing to two to three times per week recently. She complains of wheezing and dry cough as well. She is allergic to penicillin, dust, and perfumes. She is known to have hypertension. She has a history of nasal polyps removal. Her physical exam demonstrates expiratory wheezes. Chest X-ray is hyperinflated and spirometry confirms the presence of reversible airway obstruction. This approach of examination is very convenient to both students and examiners. It is structured and standardized. We were successfully able to avoid almost all disadvantages associated with a long case format. The majority of our students enjoyed the exam from personal and written feedback we received after the exam.